Functionally stable plasminogen activator inhibitor-1 in a family with cardiovascular disease and vitiligo - TOKSOY ÖNER, EBRU; DELİL, KENAN (SPRINGER, 2014)
Vitiligo is a common skin condition with a complex pathophysiology characterized by the lack of pigmentation due to melanocyte degeneration. In this study, we investigated PAI-1 antigen (Ag) and activity levels in a 34 year old male with extensive vascular disease, alopecia areata and vitiligo. Fasting PAI-1 Ag and activity levels were measured at 9 a.m. in the subject and family members. Both PAI-1 Ag (67 +/- A 38 vs. 18.6 +/- A 6.5 ng/ml, P < 0.001) and specific activity (15.8 +/- A 10.0 vs. 7.6 +/- A 6.0 IU/pmol, P < 0.04) levels of PAI-1 were moderately elevated in subjects compared to the controls. PAI-1 kinetic studies demonstrated a markedly enhanced stability of plasma PAI-1 activity in the family members. Specific activity at 16 h was significantly higher than expected activity levels (0.078 +/- A 0.072 vs. 0.001 +/- A 0.001 IU/ng/ml, P < 0.001). While the exact mechanism of increased stability of PAI-1 activity in vitiligo is not known, it is likely due to post-translational modifications or increased binding affinity for a stabilizing cofactor. In conclusion, enhanced stability of PAI-1 may contribute to the pathophysiology of vascular disease and associated melanocyte degeneration. Systemic or local treatment with PAI-1 inhibitors may offer a potential treatment alternative to the near orphan status for vitiligo drug development.
Keywords: Vitiligo; PAI-1 stability; Fibrinolysis; ALOPECIA-AREATA; TRANSGENIC MICE; PAI-1; PATHOGENESIS; POLYMORPHISM; EXPRESSION; STABILITY; MIGRATION; PROMOTER